Komitmen Organisasi Memediasi Antara Pengaruh Kepuasan Kerja dan Kepemimpinan Transformasional Terhadap Kinerja pada Karyawan Industri Otomotif Kota Makssar - Rismawati; Hardani Widhiastuti; Rusmalia Dewi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze how job satisfaction and transformational leadership affect employee performance at Industri Otomotif Kota Makassar, with organizational commitment as an intervening variable. This study involved 40 employees as respondents, who were selected using saturated sampling techniques. Data was collected across three scales to measure transformational leadership, organizational commitment, and job satisfaction. In addition, employee performance is measured using performance assessments that apply at Industri Otomotif Kota Makassar. Data analysis was carried out with the SmartPLS 4.0 2024 program. The results of this study show that job satisfaction has a significant effect on performance as shown with a p-value of 0.002<0.05, transformational leadership has a significant effect on performance with a p-value of 0.036<0.05, organizational commitment has a significant effect on performance with a p-value of 0.041<0.05, job satisfaction has a significant effect on organizational commitment with a value of 0.0410.05, job satisfaction has a significant effect on organizational commitment with a value of 0.0410.05, and job satisfaction has a significant effect on organizational commitment with a p-value of 0.0410.05, and job satisfaction has a significant effect on organizational commitment with a p-value of 0.041<0.05. P-value 0.004<0.05, transformational leadership has a significant effect on organizational commitment with a significant P-value of 0.010<0.05. The role of organizational commitment as a mediator can be seen in job satisfaction which shows a significant influence on employee performance with a p-value of 0.043<0.05. The role of organizational commitment as a mediator can be seen in transformational leadership which shows a significant influence on employee performance with a p-value of 0.044<0.05.